(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2009)
The trivialization of the political discourse makes the contemporary Croatia an awkward sample for revisiting the state of nationalism and antagonism as the symptom of its post-Yugoslav condition. In their frozen and perplexed shape, many of the items "formerly known" as crucial for the nationaloriented politics, are now nonchalantly left to the pop-cultural elaboration. With the two intriguing examples of Croatian pop-ideology we are showing the paradoxes of the cultural critique coping with the mimicrycal nature of its traditional object. The question of "over" or "under-interpretation" of its quasipolitical content, thus spreads into the entirety of social understanding of transitional cultures, which are swapping the ideological for the procedural reason of their political normality.